2013
DOI: 10.3310/hsdr01090
|View full text |Cite
|
Sign up to set email alerts
|

Can an epilepsy nurse specialist-led self-management intervention reduce attendance at emergency departments and promote well-being for people with severe epilepsy? A non-randomised trial with a nested qualitative phase

Abstract: ObjectivesTo (1) describe the characteristics and service use of people with established epilepsy (PWE) who attend the emergency department (ED); (2) evaluate the economic impact of PWE who attend the ED; (3) determine the effectiveness and cost-effectiveness of an epilepsy nurse specialist (ENS)-led self-management intervention plus treatment as usual (TAU) compared with TAU alone in reducing ED use and promoting well-being; (4) describe patients' views of the intervention; and (5) explore their reasons for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 122 publications
0
22
0
Order By: Relevance
“…In England alone, there are around 100 000 visits to EDs for epilepsy each year 5. The cost of providing this care in 2012/2013 was >£56 million 9. The ambulance service has a critical role in helping achieve any reduction, as nearly all seizure patients (∼90%) attending ED arrive by emergency ambulance 10.…”
Section: Introductionmentioning
confidence: 99%
“…In England alone, there are around 100 000 visits to EDs for epilepsy each year 5. The cost of providing this care in 2012/2013 was >£56 million 9. The ambulance service has a critical role in helping achieve any reduction, as nearly all seizure patients (∼90%) attending ED arrive by emergency ambulance 10.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that in 2008/2009, there were 37 140 NHS hospital admissions for which epilepsy was the primary diagnosis. Six out of seven admissions for epilepsy are made on an emergency, rather than planned basis 33. The average episode cost was estimated at £1514,34 which indicated a total annual inpatient cost of £56.2M.…”
Section: Discussionmentioning
confidence: 99%
“…According to the census from 2011, London's population was just under 60% white, 19% Asian/Asian British and 13% black/African/Caribbean/black British. 172 In the context of a prior study, 173 we described that felt-stigma was associated with higher usage of EDs for seizures in PWE. Non-white individuals were less likely to participate in a study of nurse-specialist education aimed at increasing self-management among those attending an ED.…”
Section: Social Isolation and Stigmamentioning
confidence: 91%
“…20 In general, there are few studies on the cost of epilepsy. 12,173 In comparison, type I and type II diabetes mellitus cost about £9.8B a year in direct costs for the NHS for 3.8 million patients, 179 which extrapolates to approximately £2500 per year per patient.…”
Section: Cost Of Epilepsy and Service Usementioning
confidence: 99%